Dynamic Governance in public service: Case Study on Bojonegoro Traffic Information Center application - Afida, Nurul Izzah; Ana Kumalasari; Ida Swasanti; Mohamed Alamin Ibrahim Yosif4 (Jurnal Administrasi Publik (Public Administration Journal), 2025)
The Bojonegoro Traffic Information Center (Bojonegoro TIC) application is an innovative application managed by the Transportation Agency to facilitate the process of providing public information services in the field of traffic. The government is expected to be able to implement dynamic governance, by the times but not ignoring the needs of the community. Focusing on a case study where the Bojonegoro Traffic Information Center application has been launched since 2018 and has undergone three stages of renewal, but the people of Bojonegoro city still do not know the existence of the Bojonegoro Traffic Information Center application in providing public information services. There are still several obstacles such as in 2022 the weakness of CCTV real-time data that cannot function for almost a year, there are still many people who are in remote areas, and also people who are old are not accustomed to using cellphones as a source of public information services, they think that cellphones are only limited to communication tools. This study aims to determine the dynamic governance of service delivery through the Bojonegoro Traffic Information Center application according to Neo & Chen 2007, where there are three dynamic governance capabilities: Thinking Ahead, Thinking Again, and Thinking Across. The results of the study have thought ahead by preparing public services through one service application and creating innovations to bring services closer to the community, but also have thought again by conducting regular evaluations and thinking across borders by adopting thoughts from other regions by implementing directly on the application so that it can support public services to the community.